Augmented Reality as Early Childhood Learning Media: Environment Theme (Edukasi, 2022)
Augmented Reality is a result of technological advances that can be used to improve learning outcomes. The purpose of this study is to provide an overview of the development of learning media based on Augmented Reality on the theme of my environment with the discussion of saving in the bank and buying and selling in the market which is applied to early childhood learning. The method used is Research and Development with the following stages: (1) preliminary investigation, (2) design, (3) realization/construction, (4) test, evaluation, and revision. Expert judgment is used in the development of this product, followed by trials with early childhood students to get various responses as input for improvement. The results of the assessment carried out by experts are included in the category of good scores and are suitable for use. The response from the students was positive, they preferred the material to be presented in 3D accompanied by an audio explanation.